Provenance and Climatic Implications of the Middle-Pleistocene Loess Deposit, Southern China - Fan, Qingbin; Liao, Jie; Li, Yan; Ye, Wei; Wang, Tao; Feng, Xiao (Frontiers in Earth Science, 2021)
The middle-Pleistocene Xiashu loess deposit in the lower reaches of the Yangtze River (LRYR), southern China, may yield evidence with significant climatic and environmental significance. However, its provenance remains controversial. In this study, grain size analysis, and quartz grain surface microtextural and morphological observations, enabled comparison of the provenance of loess in the LRYR with those on the Loess Plateau in northern China. The results show that the grain size characteristics of the Xiashu loess do not follow the coarse-fine NW-SE trend in northern China, and the surface microtextures of the quartz grains in the Xiashu loess are distinctly different from those on the Loess Plateau in northern China, indicating that the loess deposits in the two regions have different provenances. The Gobi Desert in inland northwestern China are not considered as the primary provenance of the Xiashu loess. Instead, the adjacent floodplains in the LRYR, the alluvial plains of the Huai River and the Yellow River to the north during glacial periods are suggested as the dominant source materials for the Xiashu loess. Under the background of middle-Pleistocene climate transition (MPT), regional aridity and a strengthened east Asian winter monsoon (driven by global cooling and the rapid uplift of the Tibetan Plateau) were considered as the primary drivers for the development of the Xiashu loess. The sustained eolian loess accumulation represent a regional response of the northern subtropical area of southern China to the MPT global cooling event at around 0.9 Ma.